New observational method framework for embedded walls. Issue 3 (9th August 2018) - Hardy, Stuart; Nicholson, Duncan; Ingram, Peter; Gaba, Asim; Chen, Ying; Biscontin, Giovanna
Abstract : This paper introduces the new holistic observational method (OM) framework described in the Construction Industry Research and Information Association's guide C760 – the new revision to the Embedded Retaining Walls design guide C580. This new OM framework is described by four approaches, and these are explained with reference to case histories. The maximum benefit is achieved by back-analysing case histories in similar ground conditions to derive the most probable soil parameters. These parameters can then be used in an ab initio design to maximise saving in the wall thickness, toe embedment and propping requirements. A contingency plan is based on characteristic soil parameters, and this may involve additional propping. The term ' ipso tempore ' is introduced for the circumstance where wall redesign occurs after construction starts. This may be to achieve saving in propping where movements are much smaller than predicted. Alternatively, additional propping or ground treatment may be required, and this is consistent with Peck's 'best-way-out' approach.